Conceptualising External and Internal Quality Assurance in Higher Education: A Pragmatist Perspective - Ansah, Francis (International Journal of African Higher Education, 2016)
The traditional tension between external and internal quality assurance implementation in higher education appears to be declining, based on a rethinking of the relationship between the two concepts. Although there are quality assurance agencies that still consider external and internal quality assurance as separate entities, most quality assurance agencies now regard the two concepts as complementary. In this paper, a case is put that the present rethinking of external and internal quality assurance in most higher education settings is guided by pragmatism, but not explicitly acknowledged in the literature. For a better appreciation of pragmatists’ influence on the current understanding of the relationship between external and internal quality assurance in higher education, this paper provides a further pragmatist conceptualisation of the two concepts to enhance stakeholders’ appreciation of employing a pragmatist approach to quality assurance practices in higher education. The conceptualisation is done through a pragmatist analysis of selected international accounts on higher education quality assurance. The paper concludes that pragmatism helps to understand external and internal quality assurance as nested concepts with reciprocities of accountability and improvement roles, and influences which call for alignment of perspectives through negotiations and settlements in order to focus on their practical relevance for implementation in higher education. La tension traditionnelle entre l’implémentation de systèmes d’assurance qualité interne et externe dans l’enseignement supérieur semble s’affaiblir grâce à la reconsidération de la relation entre ces deux concepts. Bien qu’il existe des agences d’assurance qualité qui continuent à considérer les assurances qualité interne et externe comme deux entités distinctes, la plupart des agences considèrent désormais qu’elles sont complémentaires. Cet article soutient que la nouvelle manière de penser les assurances qualité interne et externe dans l’enseignement supérieur est guidée par un souci de pragmatisme mais est encore peu reconnue dans la littérature. Pour mieux apprécier l’influence des pragmatistes sur la compréhension actuelle de la relation entre les assurances qualité interne et externe, cet article offre une conceptualisation pragmatique approfondie de ces deux concepts dans le but d’augmenter l’appréciation des parties prenantes pour l’utilisation d’une telle approche. La conceptualisation proposée provient d’une analyse pragmatique d’un choix d’expériences internationales en matière d’assurance qualité pour l’enseignement supérieur. En conclusion, cet article affirme que le pragmatisme aide à comprendre les assurances qualité interne et externe comme des concepts imbriqués qui ont des rôles réciproques en ce qui concerne la responsabilisation du système et son amélioration. Ces rôles ainsi que l’influence exercée par ces deux types d’assurance qualité requièrent des négociations et accords, pour s’accorder sur les perspectives et pouvoir ensuite se concentrer pleinement sur la pertinence pratique de leur implémentation dans les systèmes d’enseignement supérieur.